An exploration of how Professional Learning Communities can contribute to the development of teachers' capabilities and valued functionings in teaching environmental content knowledge in the Life and Living strand in Grade 8 Natural Sciences - Thomas, Kgomotso Emily (Rhodes University, Faculty of Education, Department of Education, 2019)
The study explored how professional learning communities can contribute to the development of teachers' capabilities and achievement of valued functionings related to teaching environmental content knowledge in the Life and Living strand in Grade 8 Natural Sciences. This is in the context of the Curriculum Assessment and Policy Statement (CAPS), which is a content-referenced curriculum that requires active and critical approaches to learning, and to environment and sustainability content. This study is designed as a qualitative case study of a professional support forum (PSF) in the Mahikeng sub-district, in North West. The study made use of questionnaires, observations, interviews and document analysis as data generation methods. The Capability Approach was used as a theoretical and conceptual framework to explore teachers' valued functionings, as well as the conversion factors related to those functionings. A functioning is defined as what a person values to be or do, hence the term valued beings and doings has been used interchangeably with the term valued functionings throughout the study. The analysis of data was done in three phases. Phase one analysis was inductive with the data from questionnaires, classroom observations, document analysis (work schedules and lesson plans or preparation books). The purpose of this phase was to answer the first research sub-question of how teachers teach environmental content. Phase two was a deductive analysis, and the purpose was to present teachers' valued beings and doings in teaching environmental content, and in belonging to the PSF. The last phase of analysis was abductive, and it employed the theoretical framework of Sen's Capability Approach to get a deeper understanding of factors that either enabled or constrained teachers' valued beings and doings associated with their capabilities. The study found that teachers have gaps in their environmental content knowledge in the Life and Living strand grade 8 Natural Sciences. This was mainly as a result of teachers not having relevant qualifications, and/or not having any professional development in teaching the environmental content knowledge. Secondly, teachers used traditional methods which were teacher-centred to teach environmental content knowledge. The gaps in the environmental content knowledge were constraints to how the teachers taught environmental content in their classrooms. Teachers' valued beings and doings related to teaching environmental content were discussed under the three conversion factors of the capability approach: personal, social and environmental conversion factors. The study found that teachers' qualifications, experiences, passion for environmental content topics, level of confidence, teaching and learning resources, learners' interest and participation, support, classroom and schools' environment were among conversion factors that either enabled or constrained teachers' valued functionings in teaching environmental content Findings also revealed that teachers have different valued functionings related to belonging to the PSF: shared responsibilities, shared values and vision, collaboration, and discussion of subject content. The conversion factors related to these functionings were found to be learning space, time and duration of the PSF, activities in the PSF, teaching and learning resources, teaching experience, and facilitation. The study recommends that teachers' professional development programmes should promote subject content discussions as well as group and individual learning. They should also create supportive conditions that will expand teachers' capabilities in teaching environmental content knowldge. Lastly, the teachers' professional development programmes should explicitly take into account teachers' valued functionings and conversion factors that can enable teachers to develop their professional capabilities.
Keywords: Teachers -- Training of -- South Africa; Teachers -- In-service training -- South Africa; Science teachers -- In-service training -- South Africa; Science -- Study and teaching (Secondary) -- South Africa; Environmental education -- South Africa